Extensive blooming artifact predicts no recanalization after intravenous thrombolysis. (26th December 2015) - Yan, S.; Chen, Q.; Zhang, X.; Xu, M.; Han, Q.; Shao, A.; Liebeskind, D. S.; Lou, M.
Abstract : Background and purpose: Hemosiderin exhibits a stronger T2 shortening effect than deoxyhemoglobin. The extent of the 'blooming artifact' may therefore reflect a composition of different iron forms. Our aim was to investigate the relationship between extent of susceptibility vessel sign (SVS) width beyond the lumen and middle cerebral artery (MCA) recanalization. Methods: Clinical and imaging data from consecutive acute ischaemic stroke patients with MCA occlusion who underwent susceptibility‐weighted imaging (SWI) before intravenous thrombolysis were examined. The source images of magnitude and angiography were used to obtain the width of SVS and MCA at the interface, respectively. Results: The presence of MCA SVS was observed in 64 patients on initial SWI scans and recanalization was observed in 30 (46.9%) patients. The overestimation ratio of thrombus width on SWI was an acceptable predictor for no recanalization [odds ratio 1.360 per 0.1; 95% confidence interval (CI) 1.093−1.691; P = 0.006]. The optimal cut‐off point was identified at 1.943, and this yielded a sensitivity of 67.6% and a specificity of 86.7%. Extensive blooming artifact, defined as overestimation ratio ≥2, independently predicted no recanalization (odds ratio 9.687, 95% CI 1.974−47.545; P = 0.005) and unfavorable outcome (odds ratio 4.916, 95% CI 1.049−23.051; P = 0.043). Conclusions: The extent of SVS width beyond the lumen might reflect the content of hemosiderin. An extreme overestimation ratio might indicate aged thrombus, which may be resistant to thrombolysis.